2019
DOI: 10.3390/antiox8100438
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Extraction of Ricinine from Ricinus communis Leaves

Abstract: The alkaloid ricinine (3-cyano-4-methoxy-N-methyl-2-pyridone) is found in different parts of the Ricinus communis plant and is known to possess several bioactive properties, including strong antioxidant activity. In this study, a new microwave-assisted extraction (MAE) method was developed for the recovery of ricinine from R. communis leaves. The extraction variables studied were extraction temperature (between 125 °C and 175 °C), microwave power (between 500 W and 1000 W), extraction time (between 5 min and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…On the other hand, Flores-Macías et al [29] found concentrations in the methanolic extracts of areal parts of R. commuis (894, 101, 103 and 104.2 µg mL −1 ). In this work, the concentrations of the methanolic extracts were similar to those reported by Nebo et al [32], where the concentrations ranged from 0.92 to 1.58 mg g −1 . However, the values for the concentrations in this study were lower than those reported by Flores-Macías et al [29], which were between 9.17 and 18.25 µg mL −1 .…”
Section: Effectiveness Of Sa As An Elicitor or Secondary Metabolitessupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, Flores-Macías et al [29] found concentrations in the methanolic extracts of areal parts of R. commuis (894, 101, 103 and 104.2 µg mL −1 ). In this work, the concentrations of the methanolic extracts were similar to those reported by Nebo et al [32], where the concentrations ranged from 0.92 to 1.58 mg g −1 . However, the values for the concentrations in this study were lower than those reported by Flores-Macías et al [29], which were between 9.17 and 18.25 µg mL −1 .…”
Section: Effectiveness Of Sa As An Elicitor or Secondary Metabolitessupporting
confidence: 89%
“…The ricinine concentrations in the control group were similar to those reported by Nebo et al [32] (1.3921 to 1.442 mg g −1 ) in leaves of the methanolic extract of R. communis. On the other hand, Flores-Macías et al [29] found concentrations in the methanolic extracts of areal parts of R. commuis (894, 101, 103 and 104.2 µg mL −1 ).…”
Section: Effectiveness Of Sa As An Elicitor or Secondary Metabolitessupporting
confidence: 89%
“…Selecting the appropriate extraction technology and optimizing relevant process parameters can greatly reduce the time and economic costs of extraction processes [11]. There are many methods for extracting the active ingredients of natural medicines, including solvent extraction (SE) [12], steam distillation (SD) [13], ultrasonic-assisted extraction (UAE) [14], microwave-assisted extraction (MAE) [15], supercritical-fluid extraction (SFE) [16], enzyme hydrolysis (EH) [17], and other methods [18]. Among them, UAE has the advantages of simple extraction, convenient operation, high extraction efficiency, and short extraction time, making it the most commonly used process [19].…”
Section: Introductionmentioning
confidence: 99%
“…[2] One class of these bioactive natural compounds is the 4hydroxy-2-pyridone (HPO) alkaloid. [3] HPO derivatives are sixmembered heterocycles that are mainly produced by fungi [4] or some plants [5] and cause pathogenicity or incapacitate insects and regulate insect behavior. [6] These compounds have many biological activities such as antifungal (Oxysporidinone; A), [7] antibiotic (Ricinine; B), [8] insecticidal (Ilicicolin; C), [9] cytotoxic, [10] neurotoxic, [11] anti-proliferative, [12] antibacterial, [13] and anti-oxidant (Mannich base of 4-hydroxy pyridine; D) [14] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%